2012
DOI: 10.5194/bg-9-4487-2012
|View full text |Cite
|
Sign up to set email alerts
|

A model for simulating the timelines of field operations at a European scale for use in complex dynamic models

Abstract: Complex dynamic models of carbon and nitrogen are often used to investigate the consequences of climate change on agricultural production and greenhouse gas emissions from agriculture. These models require high temporal resolution input data regarding the timing of field operations. This paper describes the Timelines model, which predicts the timelines of key field operations across Europe. The evaluation of the model suggests that while for some crops a reasonable agreement was obtained in the prediction of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…Also, global data sets on crop rotations (Kollas et al, 2015), the timing of field operations (Hutchings et al, 2012), and crop residue management, as well as livestock management systems would be an asset, as the interaction of different cropping systems and natural vegetation is now further increased via the nitrogen cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Also, global data sets on crop rotations (Kollas et al, 2015), the timing of field operations (Hutchings et al, 2012), and crop residue management, as well as livestock management systems would be an asset, as the interaction of different cropping systems and natural vegetation is now further increased via the nitrogen cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Fixed and oversimplified temporal profiles (monthly, daily, or hourly resolved) are often used (Van Pul et al, 2009). In this section, we outline how we explicitly described the temporal allocation of ammonia emissions from manure and fertilizer application, grazing, animal housing and manure storage based on the concepts of Skjøth et al (2004), Gyldenkaerne et al (2005) and Hutchings et al (2012).…”
Section: Temporal Allocatormentioning
confidence: 99%
“…Emissions from some activities are short term and highly variable, such as manure and fertilizer application, while some other activities contribute long term and less variable emissions, such as animal housing and manure storage. Many factors influence the variability of agricultural ammonia emissions (Battye et al, 2003;Dennis et al, 2010;Hutchings et al, 2012;Pinder et al, 2004Pinder et al, , 2006, including: https://doi.org/10.5194/acp-2019-979 Preprint. Discussion started: 2 March 2020 c Author(s) 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Senthilkumar et al (2015) highlighted the link between sowing, harvesting dates and water scarcity. Hutchings et al (2012) demonstrated the importance of the timing of field operations for complex dynamic carbon and nitrogen models. However, the timing of operations is often derived from rough regional estimates, or from farmers' enquiries further extrapolated to cover the whole catchment.…”
Section: Crop Sowing Datementioning
confidence: 99%